Ecological indicators from spatial statistics to describe the Atlantic fangtooth moray distribution in the Mediterranean Sea. Issue 7 (1st September 2022) - Perzia, Patrizia; Spinelli, Andrea; Interdonato, Filippo; Castriota, Luca
Abstract: Considering the rapid diffusion and potential impacts of invasive non‐indigenous species on biodiversity, it is crucial to investigate invasion mechanisms to identify their spread, settlement, and expansion areas. Enchelycore anatina, the Atlantic fangtooth moray of uncertain introduction pathway, recently invaded the eastern Mediterranean Sea. In the present study, specimens of E. anatina were observed in the Strait of Messina (Sicily), during 2017–2018 and records were reported. Through ecological indicators elaborated with Geographic Information System spatial–temporal statistics, E. anatina spatial–temporal distribution in the Mediterranean Sea was examined. Evidence of non‐occasional presence of this species in that area has been confirmed by the spatial statistics that suggested an established population in the central Mediterranean Sea and settlement areas along the Turkish, Levantine, and Sicilian Ionian coast. The resulting spatial structure suggested its human‐mediated introduction. The ecological indicators used in this study proved to be useful for the comprehension of the invasion history of E. anatina and might be applied to disentangle the history of other invasive species.